(3GdLGeY TQM GdeOhfI hGdeNJdWIs - (3eMeO GdJejeis; (3CHh HcQ eMeO Hf YHO Gddg Hf jhfS GdJejej GdUbdj,J (B451 (3g` s ((3GdeOQSI GdUGMHjI GdYRjRjI GdUahjI s)
(3ChdgG (B:s
(3cJGH GdeOjGf ef GdLGeY MHS GdeOjGf heWGdHJg hGdQab Hg hGdJTOjO Ydjg s
(3BNQgG (B:s
(3Je cJGH GdUObI ef GdLGeY HMeO Gddg hHJeGeg jJe GdLRA GdMGOi YTQ ef GdLGeY jJdhg ai GdMGOi YTQ cJGH GdgHI hGdgHGJ hGdMeO ddgq s
(3HChd GdfSNI agQS ehVhYGJ GdLRAs
(3Ydi dhMI GdYfhGf JedcGJs
(3cJHJ GdYfhGfGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
Keywords: (3Gdabg GdeGdcjs